New species and synonymy in the genus Corotoca Schiødte, 1853 (Coleoptera, Aleocharinae, Corotocini) - Zilberman, Bruno (Zootaxa, 2018)
Corotoca Schiødte, 1853 is a Neotropical genus of termitophiles beetles, with five species, and its description marks the first record of insects associated with termites. A new species, Corotoca fontesi sp. nov., from Brazil, is described and illustrated, and a taxonomical problem regarding to the identification and nomenclatural status of two species, Corotoca phylo Schiødte, 1853 and Corotoca seeversi Fontes, 1977, is solved. Therefore, Corotoca seeversi is proposed as a new junior synonym of C. phylo, and the material identified as C. phylo housed in the Museum of Zoology of the University of São Paulo, Brazil (MZUSP) is recognized as a new species, Corotoca fontesi sp. nov. New morphological and sexual dimorphism data in the species, and solution of some messy informations about the genus present in the literature are also present.